Mode specific dynamics of the H2 + CH3 → H + CH4 reaction studied using quasi-classical trajectory and eight-dimensional quantum dynamics methods - Wang, Yan (2015)
An eight-dimensional quantum dynamical model is proposed and applied to the title reaction. The reaction probabilities and integral cross sections have been determined for both the ground and excited vibrational states of the two reactants. The results indicate that the H2 stretching and CH3 umbrella modes, along with the translational energy, strongly promote the reactivity, while the CH3 symmetric stretching mode has a negligible effect. The observed mode specificity is confirmed by full-dimensional quasi-classical trajectory calculations. The mode specificity can be interpreted by the recently proposed sudden vector projection model, which attributes the enhancement effects of the reactant modes to their strong couplings with the reaction coordinate at the transition state.